2000
DOI: 10.1177/001440290006600204
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Demography of Childhood Poverty and Disability

Abstract: This article presents childhood disability prevalence trends and their interaction with economic status. Estimates derived from National Health Interview Survey data (1983–1996) indicate a significant increase in childhood disability rates. Increased risk for disability was among constituencies defined by poverty and single-parent families. Analysis suggests three dynamics: (a) greater risk in single-parent households, (b) no incremental risk associated with racial or ethnic status after controlling for povert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(161 citation statements)
references
References 20 publications
(18 reference statements)
7
150
0
4
Order By: Relevance
“…By contrast, among the children without disabilities in the same age range, only 16% are living in poverty (Fujiura & Yamaki, 2000).…”
Section: Prevalencementioning
confidence: 96%
See 1 more Smart Citation
“…By contrast, among the children without disabilities in the same age range, only 16% are living in poverty (Fujiura & Yamaki, 2000).…”
Section: Prevalencementioning
confidence: 96%
“…As of 1997, more than a fifth of American children lived in families with cash incomes below the poverty level (Dalaker & Naifeh, 1998). Significantly, recent demographic studies have found a growing relationship between poverty and risk for disability (Fujiura & Yamaki, 2000;Kaye, LaPlante, Carlson, & Wenger, 1996;Seelman & Sweeney, 1995). For example, the longitudinal estimates done by Fujiura and Yamaki (2000) indicated a significant increase in the rate of childhood disability over the past 14 years among constituencies defined by poverty and singleparent headed families.…”
mentioning
confidence: 99%
“…Research by Algood, Hong, Gourdine and Williams (2011), Jaffee, Caspi, Moffitt, PoloTomás and Taylor (2007), and Fujira and Yamaki (2000) indicates that children who live in poverty are at greater risk of being abused than children who do not live in poverty. It is already clear that the participant families come from deprived circumstances (Theme 1); and the literature indicates that such families are at risk of child abuse and neglect, which was found to be the case in this research.…”
Section: Child Abuse/neglect/statutory Interventionmentioning
confidence: 99%
“…Although disabilities clearly contribute to the increased likelihood of living in poverty in the United States, poverty also increases the risk of disability. Being born in poor families elevates the risk that a child will have impairments (Fujiura & Yamaki, 2000), most likely because of reduced access to adequate and appropriate health care (both prenatally and throughout childhood); reduced access to sufficient nutrition; and the array of environmental risks that accompany poverty.…”
Section: Women With Disabilities and Povertymentioning
confidence: 99%